Role of MRI and surgical excision in long-standing diffuse-type GCTTS of the flexor tendon sheath - Antonios Michailidis, MD; Ioannis Tsifountoudis, MD, PhD; Dimitrios Kitridis, MD, FEBOT, MSc, PhDc; Eleni Karagergou, MD, PhD; Alexandros Givissis, MD; Panagiotis Givissis, MD, PhD (Radiology Case Reports)
Diffuse-type giant cell tumor of the tendon sheath (GCTTS) is a rare, benign, yet locally aggressive soft tissue tumor commonly affecting the hand. This case report presents a 55-year-old male with a 5-year history of GCTTS in the flexor tendon sheath of the long finger. MRI played a critical role in both diagnosis and surgical planning, revealing key features such as the tumor's 10 cm length, hemosiderin deposition, and blooming artifacts. The patient underwent successful surgical excision with no recurrence at the 1-year follow-up. This case underscores the significance of MRI in preventing functional impairment and reducing recurrence risk in diffuse-type GCTTS.